The combination therapy with alfacalcidol and risedronate improves the mechanical property in lumbar spine by affecting the material properties in an ovariectomized rat model of osteoporosis - Ito Masako; Umakoshi Yukichi; Nakano Takayoshi; Miyabe Sayaka; Shiraishi Ayako; Mihara Masahiko (BMC Musculoskeletal Disorders, 2009)
Abstract Background We conducted the present study to investigate the therapeutic effects of a combination treatment of alfacalcidol (ALF) and risedronate (RIS) on the bone mechanical properties of bone and calcium (Ca) metabolism using an ovariectomized (OVX) rat model of osteoporosis. Methods Female Wistar rats were OVX- or sham-operated at 40 weeks of age. Twelve weeks post-surgery, rats were randomized into seven groups: 1) sham + vehicle, 2) OVX + vehicle, 3) OVX + ALF 0.025 μg/kg/day, 4) OVX + ALF 0.05 μg, 5) OVX + RIS 0.3 mg, 6) OVX + RIS 3.0 mg, 7) OVX + ALF 0.025 μg + RIS 0.3 mg. Each drug was administered orally five times a week for 12 weeks. After treatment, we evaluated the mechanical properties of the lumbar vertebra and femoral midshaft. In the lumbar vertebra, structural and material analyses were performed using micro-computed tomography (micro-CT) and microbeam X-ray diffraction (micro-XRD), respectively. Biochemical markers in serum and urine were also determined. Results (1) With respect to improvement in the mechanical strength of the lumbar spine and the femoral midshaft, the combination treatment of ALF and RIS at their sub-therapeutic doses was more effective than each administered as a monotherapy; (2) In the suppression of bone resorption and the amelioration of microstructural parameters, the effects of ALF and RIS were considered to be independent and additive; (3) The improvement of material properties, such as microstructural parameters and the biological apatite (Bap) c-axis orientation, contributed to the reinforcement of spinal strength; and (4) The combination treatment of ALF and RIS normalized urinary Ca excretion, suggesting that this treatment ameliorated the changes in Ca metabolism. Conclusion These results demonstrate that the combination treatment of ALF and RIS at their sub-therapeutic doses can improve the mechanical properties of the spine as well as the femur and ameliorate changes in Ca metabolism in an animal model of osteoporosis, suggesting that the combination treatment of ALF and RIS has a therapeutic advantage over each monotherapy for the treatment of osteoporosis.